Efficacy and safety of testosterone replacement gel for treating hypogonadism in men: Phase III open‐label studies. (10th March 2017) - Belkoff, L.; Brock, G.; Carrara, D.; Neijber, A.; Ando, M.; Mitchel, J.
Summary: Efficacy and safety of testosterone gel 2% (TG) were evaluated in two phase 3, open‐labelled, single‐arm, multicentre studies (000023 and extension study 000077). Hypogonadal men having serum testosterone levels <300 ng/dl at two consecutive measurements were included. Study duration was 9 months (000023: 3 months; 000077: 6 months). Starting dose of TG (46 mg) was applied on upper arm/shoulder. The primary endpoint (000023) was responder rate (subjects with average 24‐hour serum testosterone concentration 300‐1050 ng/dl on Day 90). Study 000077 evaluated the safety of TG in patients rolling over from study 000023 over a period of 6 months. Of 180 subjects in 000023, 172 completed and 145 rolled over to 000077, with 127 completers. The responder rate was 85.5%. Fewer subjects in 000077 (12.7%) versus 000023 (31.8%) had maximum testosterone concentration ( C max ) >1500 ng/dl, with no significant safety concerns. Significant improvements in sexual function and quality of life were noted in both studies. Subjects experienced few skin reactions without notable increases in prostate‐specific antigen and haematocrit levels. TG was efficacious with an acceptable safety profile. C max >1500 ng/dl did not exhibit distinct impact on safety parameters. However, further optimisation of titration schema to reduce C max is warranted while maintaining the average steady state total testosterone concentration.